MEMAHAMI PEMBERHENTIAN PRESIDEN (IMPEACHMENT) DI INDONESIA (Studi Perbandingan Pemberhentian Presiden Soekarno dan Presiden Abdurrahman Wahid) - Miftachus Sjuhad, Fatkhurohman dan (Jurnal Konstitusi, 2010)
Empirically, the journey of the Indonesian government sees the term impeachment. However, its implementation has not been well-structured, since it is merely based on the political power in the Majelis Permusyawaratan Rakyat (MPR), not on the proving mechanisme in the court. This case makes the impeachment of the President Soekarno and Abdurrahman Wahid be bad records for the history of the president impeachment in Indonesia. In the future, such an impeachment attributivelly is under the authority of the Constitutional Court.